Disruptive coloration and habitat use by seahorses - Duarte,Michele (2019)
ABSTRACT Predation avoidance is a primary factor influencing survival. Therefore, any trait that affects the risk of predation, such as camouflage, is expected to be under selection pressure. Background matching (homochromy) limits habitat use, especially if the habitat is heterogeneous. Another camouflage mechanism is disruptive coloration, which reduces the probability of detection by masking the prey’s body contours. Here we evaluated if disruptive coloration in the longsnout seahorse, Hippocampus reidi, allows habitat use diversification. We analyzed 82 photographs of animals, comparing animal and background color, and registering anchorage substrate (holdfast). We tested whether the presence (disruptive coloration) or absence of bands (plain coloration) predicted occupation of backgrounds of different colors. We also calculated the connectance between seahorse morph and background color or holdfast, as well as whether color morph differed in their preferences for holdfast. Animals with disruptive coloration were more likely to be found in environments with colors different from their own. Furthermore, animals with disruptive coloration occupied more diversified habitats, but as many holdfasts as plain colored animals. Therefore, animals with disruptive coloration were less selective in habitat use than those lacking disruptive color patterns, which agrees with the disruptive coloration hypothesis.